Uso de la palma Attalea butyracea como tienda de percha por el murciélago Uroderma bilobatum en Oaxaca, México - García-García, José Luis; Santos-Moreno, Antonio (Instituto de Ecología, A.C., 2014)
The use of tent roosts by phyllostomid bats has been poorly documented in Mexico. We report the use of tent roosts by the tent-making bat (Uroderma bilobatum) with palm fronds of Attalea butyracea in a riparian forest of the state of Oaxaca, southeastern Mexico.